1991
DOI: 10.1055/s-0038-1646451
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Generation and Fibrinolysis in the Thrombotic Thrombocytopenic Purpura and the Hemolytic-Uremic Syndrome

Abstract: SummaryProthrombin fragment 1+2 (F1+2) and thrombin-antithrombin complexes (TAT), as well as other coagulation and fibrinolysis parameters, were studied in a series of 13 patients affected by thrombotic thrombocytopenic purpura (TTP) or hemolytic-uremic syndrome (HUS). Fragment F1+2 was found to be increased in all patients at diagnosis (patients' range, 1.21-19.03 nmol/1; normal limits, 0.28-1.08 nmol/1), and remained also higher than normal after treatment with plasma exchange (patients' range, 1.5-4.01 nmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…45 TM syndromes are associated with systemic lupus erythematosus and antiphospholipid antibodies, 46 and the inactivation of factor Va by activated protein C is inhibited by antiphospholipid antibodies, suggesting a pathogenic defect similar to factor V Leiden. 47,48 Abnormalities of fibrinolysis have been implicated in the pathogenesis of TM syndromes, 32,33,35,49 and activated protein C has been shown to enhance fibrinolysis indirectly by down-regulating production of thrombin and thrombin-activatable fibrinolysis inhibitor. 50 In vitro studies have shown that acceleration of fibrinolysis by activated protein C is markedly attenuated by factor V Leiden, 51 which might promote microvascular thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 TM syndromes are associated with systemic lupus erythematosus and antiphospholipid antibodies, 46 and the inactivation of factor Va by activated protein C is inhibited by antiphospholipid antibodies, suggesting a pathogenic defect similar to factor V Leiden. 47,48 Abnormalities of fibrinolysis have been implicated in the pathogenesis of TM syndromes, 32,33,35,49 and activated protein C has been shown to enhance fibrinolysis indirectly by down-regulating production of thrombin and thrombin-activatable fibrinolysis inhibitor. 50 In vitro studies have shown that acceleration of fibrinolysis by activated protein C is markedly attenuated by factor V Leiden, 51 which might promote microvascular thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Reported abnormalities of coagulation proteins in TM include increased PAI-1 activity and deficiencies of protein C, protein S, tissue plasminogen activator, and urokinase-type plasminogen activator. [32][33][34][35] Studies in kindreds with familial HUS indicate that genetic alterations of complement factor H, a plasma protein that down-regulates complement activity, are prevalent in this subset of TM patients. [36][37][38][39] Complement activation is known to induce expression of tissue factor and adhesion molecules on endothelial cells and procoagulant alterations on platelet surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Marburg, FRG). In our hands, F, + 2 refer ence range was 0.28-1.08 nmol/1, with intra-and inter assay variation coefficients of 4.3-13.7 and 5.9-17.2% [12], respectively, whereas no thrombin was further generated in vitro [12,13]. ATIII activity was mea sured according to Abildgaard et al [14].…”
mentioning
confidence: 99%
“…Forty patients undergoing 43 consecutive OLT, with ages ranging from 13 to 61 years (median 47), have been prospectively studied. Etiologies including liver cirrhosis were associated to previous hepatitis (13), alcoholism (5), and porphyria cutanea [1], whereas 8 were of unknown origin; other causes were primary biliary cirrhosis (6), hepatocarcinoma (1), and hemochromatosis (2). Acute, fulminant forms of liver failure required OLT in 4 patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation